ASSESSMENT OF SUSTAINABILITY INDICATORS OF TWO GAS- TURBINE PLANTS WITH NAPHTHA AND NAPHTHA-RFG MIXTURE AS FUELS - Arpit, Sankalp; Das, Prasanta Kumar; Dash, Sukanta Kumar (MATTER: International Journal of Science and Technology, 2020)
To enhance sustainability of any energy system exergy based sustainability indicators (exergy efficiency, waste exergy ratio, environmental effect factor and exergetic sustainability index) are used. In the present paper sustainability aspects of two GT based power plant are carried out using sustainability indicators. For this purpose, two GT1) configurations, case A (Naphtha based GT power plant) and case B (Naphtha-Residual fuel gas mixture GT 2) are taken up as case study. Results show that exergetic sustainability index obtained as for case A is higher as compared to case B.